Estimulación temprana y su incidencia en el proceso de aprendizaje en los niños de educación inicial en la Unidad Educativa “María Auxiliadora cantón Babahoyo” - Moreira Mora, Maria Laura (2019)
The Maria Auxiliadora Educational Unit was the content of the current research work. In the Educational Institution the topic of Early Stimulation. Child development is a highly complex dynamic process in which the child grows and evolves in the first 5 years of life the child develops his brain That is why we can begin to encourage your curiosity and desire to discover new things. It was evident that children in their learning have a defit in the fine motor development and in the thick motor that is why this case study is relevant to take advantage of the adaptability and learning of the human brain, especially children. With the help of early stimulation, we will be able to strengthen your child's self-esteem; They will have a good attention span and concentration. Early stimulation also allows us to form closer communication bonds within the family nucleus. In order to carry out the activities of early stimulation effectively, it is very significant to have a pleasant environment for the children who motivate them and wake up their attention. It is recommended that the environment where the early stimulation is performed has good lighting and an adequate temperature